A Rare Case of Mixed Type A Thymoma and Micronodular Thymoma with Lymphoid Stroma - Cha, Yoon Jin; Han, Joungho; Kim, Jimin; Lee, Kyung Soo; Shim, Young Mog (Journal of pathology and translational medicine, 2015)
With its rich B-cells, occasional germinal centers, and nodules of epithelial cells, MNTLS could be misdiagnosed as metastatic carcinoma in a small biopsy specimen.4 Although the histogenesis of MNTLS is not yet clarified, its medullary epithelial cells suggest MNTLS may be a variant of type A thymoma in the setting of thymic B-cell hyperplasia.1 Bcl-2, a B-cell marker, is expressed in type A thymoma and thymic carcinoma.6 We observed Bcl-2 expression in both type A thymoma and MNTLS.Stobel et alJ found that 33% of MNTLS had lymphoid stroma of a monoclonal B-cell population whereas thymic lymphoid hyperplasia or other types of thymoma had a polyclonal population of lymphocytes.Because of the monoclonal lymphoid stroma, they suggested that MNTLS might be a precursor lesion of mediastinal lymphoma.7 In the present case, the lymphoid stroma was positive for both CD20 and CD3, reflecting a polyclonal lymphocyte nature.Corresponding Author Joungho Han, M.D. Department of Pathology, Samsung Medical Center, Sungkyunkwan University School of Medicine, 81 Irwon-ro, Gangnam-gu, Seoul 135-710, Korea Tel: +82-2-3410-2800, Fax: +82-2-3410-0025, E-mail: hanjho@skku.edu Received: September 2, 2014 Accepted: October 24, 2014 REFERENCES 1.